THE EFFECT OF DIGITAL TECHNOLOGY ON GOVERNMENT EFFECTIVENESS IN THE ERA OF THE INDUSTRIAL REVOLUTION 4.0 - Abdul Halil Hi. Ibrahim; Idris Sudin (RADJA PUBLIKA, 2025)
Digital transformation in the era of the Industrial Revolution 4.0 has brought fundamental changes in governance, especially in improving the effectiveness, efficiency, and transparency of public services. The utilisation of digital technologies such as e-government, big data, and artificial intelligence allows bureaucratic processes to be faster, cost-effective, and strengthen public participation in decision-making. This research uses a literature review method to analyse the influence of digital technology on government effectiveness in Indonesia, highlighting positive impacts such as service acceleration, data integration, and increased public accountability. However, the implementation of digitalisation also faces challenges, including infrastructure gaps, low digital literacy, and issues of cybersecurity and personal data protection. The results of the study show that the success of digital transformation depends on cross-sector collaboration, infrastructure strengthening, human resource development, and regulatory updates so that the benefits of digitalisation can be felt evenly and inclusively by all people.